GENETIC DIVERGENCE AND GEOGRAPHIC DISTRIBUTION OF FROGS IN GENUS FEJERVARYA FROM INDONESIA INFERRED FROM MITOCHONDRIAL 16S rRNA GENE ANALYSIS - Nia Kurniawan; Tjong Hon Djong; Tesri Maideliza; Amir Hamidy; Takeshi Igawa; Masayuki Sumida; Mahmudul Hasan (Treubia, 2014)
The Indonesian archipelago is an ideal setting for the study of speciation and biogeography. This archipelago is divided into three island groups based on zoogeography: Sundaland, Wallacea and the Australian region. In this paper we used frogs in genus Fejervarya (Bolkay) to study biogeography and examine patterns of gene flow across proposed zoogeographic boundaries. Several molecular studies on Fejervarya species from Indonesia have been carried out, but comparative studies among members of the genus Fejervarya have yet to be performed. In order to elucidate genetic divergence and geographic distribution of these frogs, we conducted a molecular analysis of the mitochondrial 16S rRNA gene using 179 frogs from five Fejervarya species. In total we collected from 32 localities in Sumatra, Kalimantan (Indonesian part of Borneo), Java, Bali, Sulawesi and Lesser Sunda Islands in Indonesia. Molecular phylogenetic analysis recovered 35 haplotypes and showed that frogs in the genus Fejervarya were divided into two well-supported clades. The first group were of three species, F. limnocharis, F. iskandari and F. cf. verruculosa and the other group clade consisted of Fejervarya cancrivora and Fejervarya sp. (Sulawesi-type). The average sequence divergence among these four species ranged from 1.09 to 16.03% (mean = 11.29Â±2.83%). The present results clearly show that there are five Fejervarya species in the Indonesian archipelago. Fejervarya limnocharis and F. cancrivora are widely distributed and sympatric in Sumatra, Borneo and Java. Fejervarya iskandari is not endemic to Java and also occurs in the Lesser Sundas. Fejervarya cf. verruculosa and Fejervarya sp. (Sulawesi-type) are endemic to Lesser Sunda and Sulawesi Island, respectively.